Customer Attitude Toward Smart Innovation Bed (SiNoBed) Application - Nugraha, Ananditha Zahra; Lindayani, Linlin; Mutiar, Astri; Taryudi, Taryudi; Darmawati, Irma (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aims : The purpose of this study is to examine and identify factors that influence customer attitudes towards and intention to use Smart Innovation Bed (SiNoBed). Methods : This type of research is descriptive research with a quantitative approach. Total of 136 valid questionnaires was obtained through online means. The demographic profile of the respondents reflected a balanced representation, with 50% being male and female. mean age of the participants was calculated to be 28.45(SD= 5.778 ) and 57% of the respondents, identified themselves as individuals employed in the nursing profession. Results : The findings reveal a significant relationship, indicating that customers who express favorable opinions on attributes such as price, design, quality, and usability tend to show high purchase intentions towards SinoBed. In conclusion this study reveals a significantly positive customer attitude towards the purchase interest in Sinobed. Conclusions : The study highlights the positive customer attitude towards SinoBed, highlighting the importance of factors like competitive pricing, appealing design, quality, and usability in shaping purchase intentions.